Formation mechanisms of Cr2AlB2, Cr3AlB4, and Fe2AlB2 MAB phases. Issue 8 (3rd August 2021) - Hanner, Luke A.; Kota, Sankalp; Barsoum, Michel W.
Abstract : Quenching studies of CrB-Al, CrB-Al-B and ß-FeB-Al mixtures revealed that all three undergo a topotactic transformation in the presence of Al to form Cr2 AlB2, Cr3 AlB4, and Fe2 AlB2 MAB phases, respectively. The formation mechanism is intercalation for the Cr-based compounds, and reconstructive for the ß-FeB based mixture. GRAPHICAL ABSTRACT: